The Contribution of The Libro In Matches And His Effects On Team Results in Volleyball - Sabhan, Hussein; Gameel, Soraa (Journal of Physical Education, 2008)
Volleyball is one of the sports that highly depend on skill and any weakness in one of its skills will lead to bad game results. Many changes have been introduced to the game one of them is the libro. These changes should be taken into considerations due to their great effect on the results of the game. The researchers noticed that most teams and coaches do not take the libero seriously and they don't focus on his effect on the game and in return on the game. Thus, the researchers aimed at identifying the contribution of this player on the game and the result. The researchers used the descriptive method. The subjects were 5 teams from Iraqi volleyball league for men for the season 2004 – 2005. The results showed that the libro's contribution had no positive effect on the results of the game or on the ranks of teams in the league. The researchers recommended the necessity of selecting the libro and making sure that he possesses the required physical, skill, mental and psychological characteristics. Finally they recommended training them to develop their skill, physical, tactical and mental characteristics.